(untitled) (Archives of Mechanics - Test, 2013)
The subject of the paper is the analysis of deflection of a five-layer sandwich beam under bending. The mechanical and physical properties vary through the thickness of the beam and depend on the material of each layer, which are: the metal face, binding material (the glue) and metal foam core. The main aim of the paper is to present the analytical model of the five-layer beam and to compare the results of bending analysis obtained theoretically and numerically. In the paper, a mathematical model of the field of displacements, which includes a shear effect and a bending moment, is presented. The system of partial differential equations of equilibrium for the five-layer sandwich beam is derived on the basis of the principle of stationary total potential energy. The equations are analytically solved and the formula describing the deflection of the beam is obtained. The influence of the thickness and mechanical properties of the binding layer on the deflection of the beam under bending is analysed. The comparison of the results obtained in the analytical and numerical (FEM) analysis is shown in graphs and figures.